2017
DOI: 10.1186/s12981-016-0128-5
|View full text |Cite
|
Sign up to set email alerts
|

Early virological failure and HIV drug resistance in Ugandan adults co-infected with tuberculosis

Abstract: PurposeThis cross-sectional study took place in the integrated tuberculosis (TB) clinic of a large outpatient clinic for HIV-infected patients in Kampala, Uganda. The purpose of this study was to describe the proportion of TB/HIV co-infected adults with virological failure, type and frequency of HIV drug resistance-associated mutations, and the proportion of patients with suboptimal efavirenz levels.MethodsHIV-1 plasma viral loads, CD4 cell count measurements, and efavirenz serum concentrations were done in TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
34
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 19 publications
8
34
1
Order By: Relevance
“…Furthermore, Lamivudine has a low genetic barrier. TAMs and K65R had a prevalence of 35.7% and 23.1% respectively, similar to a study done in Uganda [48] where K65R mutation had a prevalence of 25%. K65R is highly selected for in TDF containing regimens [51].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, Lamivudine has a low genetic barrier. TAMs and K65R had a prevalence of 35.7% and 23.1% respectively, similar to a study done in Uganda [48] where K65R mutation had a prevalence of 25%. K65R is highly selected for in TDF containing regimens [51].…”
Section: Discussionsupporting
confidence: 88%
“…It is also possible that most of these patients do not keep their appointments for scheduled viral load and drug resistance monitoring such that by the time they report back to the clinic, they have been on a failing regimen for quite some time. For NNRTI class, K103N mutation (53.8%) was indicated as the most prevalent mutation followed by G190A/S/E/G (30.2%) similar to a study done in sub-Saharan Africa [48] that indicated K103N (38.7%) and G190A/S/E/G (21.8%) as the most prevalent. This was anticipated given the fact that Efavirenz is highly used as the preferred NNRTI in this region and mutations K103N, G190A are among the most common single mutations that confer high-level resistance to all the firstgeneration NNRTIs [49].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These patients established on ART and developing TB are HIV failure per definition[ 27 ] and may have benefited from early switch to second line ART[ 28 ]. This underscores the importance and need of strengthening HIV programs and HIV management with early switch of those patients who present with ART failure and severely sick due to MDR-TB[ 29 ].…”
Section: Discussionmentioning
confidence: 99%